Additive Main Effects and Multiplicative Interactions Analysis of Yield Performances in Cowpea Genotypes under Ugandan Environments - Agbahoungba, Symphorien; Karungi, Jeninah; Talwana, Herbert; Badji, Arfang; Kumi, Frank; Mwila, Natasha; Edema, Richard; Gibson, Paul; Rubaihayo, Patrick (International Journal of Advanced Research (IJAR), 2017)
Yield in legumes is the result of many plant processes, which are usually expressed in yield and have been shown to be affected by management, genotype and environment. The objectives of this study were to assess the extent of genotype x environment interaction and to select the stable cowpea genotypes in Ugandan environments over seasons. Seventy-two cowpea genotypes were evaluated for yield in three locations and two seasons in Uganda. The yield data were subjected to analysis of variance and additive main effects and multiplicative interactions (AMMI) analysis. The results showed a highly significant (P<0.001) genotype by location and by year (season) interaction effects for grain yield, with 69.16% of the total variation attributable to environmental effects, 5.36% to genotypic effects and 12.74% to G x E interactions effects. Genotype MU9 had the highest yield (854.68 kgha-1) but was only adapted to specific environments (Arua 2015B and 2016A). Hence, genotypes WC 30, NE 45, NE 31, NE 51 which were equally high yielding, stable and adapted to the tested environments, and should be recommended for genetic improvement of cowpea germplasm in Uganda.
Keywords: Adaptability; AMMI; Stability; GxE interaction; Vigna unguiculata